Regional coordinators: a new teaching opportunity in family medicine training - Petek, Davorina (BMC Med Educ, 2016)
BACKGROUND: A new project on education in family medicine training was implemented last year in Slovenia by establishing regional coordinators in the specialist training programme. They are responsible for conducting regular small-group meetings with family medicine trainees. This study wanted to explore the attitudes and opinions of regional coordinators and family medicine trainees concerning this new method. METHODS: This was a qualitative study based on focus groups. The participants were regional coordinators and family medicine specialist trainees. The data were analysed based on the principles of thematic content analysis with inductive technique. RESULTS: The study revealed five themes which were the same for the analysis of transcripts of both regional coordinators and family medicine trainees: 1) Meetings with trainees; 2) Coordination; 3) Characteristics of regional coordinators; 4) Position of regional coordinators, and 5) Evaluation of regional coordinators. CONCLUSION: Participants of the study have many expectations for this new programme. They expect progress in trainees’ clinical knowledge through experience-based group learning and with the help of the tutorship role of regional coordinators. The role of regional coordinators represents a new possibility for solving problems in the training programme in their coordinating role. In future, they have the potential to develop into an expert body that supervises the quality of training. A close follow-up is necessary to see if the position of regional coordinators is adequate and if they meet the expectations of the trainees as well as their own goals. Administrative and financial support for the programme is necessary. The project is important also in enabling the adaptation of the training programme’s needs and the regional characteristics of medical care.